Almost Near $(τ_1,τ_2)$-continuity for Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
This paper presents new classes of multifunctions called upper almost nearly $(τ_1,τ_2)$-continuousmultifunctions and lower almost nearly $(τ_1,τ_2)$-continuous multifunctions. Moreover, several characterizationsand some properties concerning upper almost nearly $(τ_1,τ_2)$-continuous multifunctions and lower almost nearly $(τ_1,τ_2)$-continuous multifunctions are established.
Keywords: upper almost nearly $(τ_1,τ_2)$-continuous multifunction; lower almost nearly $(τ_1,τ_2)$-continuous multifunction